KAJIAN SOSIOLOGIS MASALAH ANAK DAN REMAJA DAN KELUARGA SEJAHTERA - Aris Lambe (Jurnal Pluralis, 2023)
Sociologically adolescent is a shift between childhood to adult. Adolescent at this point is very easily influenced by their surroundings outside our neighborhood is called unmature mind. Family is a small unit in a society, consist of father, mother, and children. Father is a figure inside a family that will become a facilty and protection for family, a supervisor function. Mother as the observer of family development by individual or group. Mothers figure is also construct love inside family and develope it into a family solidarity so it become social integrity inside family. Guiding children inside family by long time socialization and require preseverance to watch over childrens development.